Adenovirus E1B-55K interferes with cellular IκB kinase complex subunit proteins - Ip, Wing-Hang; Bertzbach, Luca D.; Schreiner, Sabrina; Dobner, Thomas (Frontiers in Immunology, 2025)
Human adenovirus (HAdV) infections can cause high mortality rates in immunocompromised patients due to the activation of unhampered cytokine storms that are mainly induced by activation of pro-inflammatory cytokines. NF-κB is a transcription factor that is involved in numerous biological processes such as regulation of cell death and proliferation, as well as the activation of innate immune responses including the expression of pro-inflammatory cytokines, chemokines, and other immune response genes. The IKK complex plays a crucial role in the NF-κB pathway by phosphorylating and activating IκB proteins, which leads to the degradation of IκB and the subsequent release and nuclear translocation of NF-κB dimers to initiate gene transcription. The host NF-κB pathway, particularly the formation of the IKK complex, is a common target for viruses to regulate host immune responses or to utilize or inhibit its function for efficient viral replication. So far, investigations of the immune response to adenovirus infection mainly focused on transduction of adenoviral vectors or high-titer infections. Therefore, the molecular mechanism of HAdV- and HAdV gene product-mediated modulation of the NF-κB response in lytic infection is not well understood. Here, we show that HAdV-C5 infection counteracts cellular IκB kinase complex formation. Intriguingly, the IKK complex protein IKKα is targeted to the nucleus and localizes juxtaposed to viral replication centers. Furthermore, IKKα interacts with the early viral E1B-55K protein and facilitates viral replication. Together, our data provide evidence for a novel HAdV-C5 mechanism to escape host immune responses by utilizing NF-κB pathway-independent nuclear functions of IKKα to support efficient viral progeny production.